Strategi Kolaboratif Dalam Manajemen Perencanaan Perusahaan Dan Perencanaan Pendidikan Dalam Layanan Bimbingan Konseling - Nabilaa Faizatuz Zuhriyah; Nina Siti Marlina (Syntax Idea)
This study examines a collaborative approach to integrating corporate strategic planning and educational planning in school counseling services. The core issue addressed is the need for better synergy between corporate managerial approaches and the education system to enhance the effectiveness of counseling services. The research aims to identify strategic elements that can be implemented in counseling planning to strengthen the structure, relevance, and efficiency of services for students. Using a qualitative method with a case study design, this study analyzes various strategic factors such as SWOT analysis, Key Performance Indicators (KPIs), and data-driven action plans. Research data were collected through in-depth interviews, observations, and document analysis from educational institutions implementing collaborative strategies. The findings indicate that integrating strategic planning improves the effectiveness of counseling services by creating a more structured system aligned with student needs and workforce demands. In addition to providing practical insights for schools in designing more adaptive counseling programs, this study contributes to the literature on cross-sector collaboration in education. The study's implications include recommendations for policymakers to promote closer cooperation between the business and education sectors to create more holistic and sustainable educational services.